Heterogeneity In Women's Trauma Histories: Impact On Substance Use Disorder Severity. Issue 3 (27th May 2023) - Gallagher, C; Brunelle, C
ABSTRACT: Trauma and substance use disorders (SUDs) frequently co-occur, especially in women. Previous studies have attempted to determine if individual differences in trauma histories could be meaningfully categorized but few studies have focused solely on women, especially those reporting substance use problems. A total of 130 women ( M age = 30.7, SD = 7.9) self reporting past-year substance use problems completed comprehensive measures assessing lifetime exposure to a variety of traumatic events as well as substance use patterns and severity. Using latent class analysis, three classes emerged, a Low Lifetime Interpersonal Trauma class (40%, n = 52), a Moderate Lifetime Interpersonal Trauma class (23.8%, n = 31) and a High Lifetime Interpersonal Trauma class (36.2%, n = 47). Groups did not vary on daily/almost daily use of different types of substances and polysubstance use frequency but were significantly different on SUD severity, with the Moderate and the High Lifetime Interpersonal Trauma classes reporting severe SUD severity in comparison to moderate severity for the Low Interpersonal Trauma class. The findings of the current study indicate that women experiencing substance use problems should receive SUD treatment in a trauma-informed manner but that not all may require integrated trauma and substance use interventions.